The impact of customer relationship management to achieve a sustainable competitive advantage for Touristic hotels ((An analytical study)) - Alaa Abd Al Hussein Radhi (Peerian Journals Publishing, 2022)
The research aims to determine the role of customer relationship management in achieving the competitive advantage of the hotels under study. The research sample included all managers of tourist hotels operating in the holy city of Karbala. A random image sample of 40 managers was selected, and the following statistical methods were also relied on (arithmetic mean, standard deviation). and relative importance) in order to give a statistical description of the researched sample. Provided to customers, followed by interest in the processes related to managing relationships with customers) and the research came out with a set of recommendations, the most important of which is working to permanently improve the quality of services provided to customers, as studies have proven that the quality of services directly affects the degree of loyalty of customers.
Keywords: Customer relationship management; sustainable competitive advantage; Touristic hotels